Evaluation of the Antibacterial and Antifungal Properties of Phragmanthera capitata (Sprengel) Balle (Loranthaceae), a Mistletoe Growing on Rubber Tree, Using the Dilution Techniques - Franklin Uangbaoje Ohikhena; Olubunmi Abosede Wintola; Anthony Jide Afolayan (The Scientific World Journal)
The alarming increase in multidrug resistance of pathogenic microorganisms to conventional drugs in recent years has prompted the search for new leads in alternative remedies in natural products. Hence, this study was aimed at evaluating the antimicrobial properties of Phragmanthera capitata, a parasitic mistletoe growing on rubber trees. The in vitro antimicrobial activities of the acetone, methanol, ethanol, and aqueous extracts were investigated using five gram-negative and five gram-positive bacteria and four fungi. A 96-well resazurin broth and agar dilution techniques were used for the determination of the Minimum Inhibitory and Bactericidal Concentrations. The antibacterial activity of the organic extracts had comparative effects on all the bacteria with a MIC of 1.25 to 5 mg/mL and MBC of 2.5 to 10 mg/mL. However, the acetone extract showed higher bactericidal effect while the aqueous extract was not active. The organic solvent extracts also showed antifungal activities on two of the fungi with a MIC of 1.25 mg/mL to 10 mg/mL. However, the aqueous extract had the highest activity inhibiting all the fungi with a MIC of ≤0.3125 to 1.25 mg/mL. The study supports the ethnomedicinal claims of P. capitata as a remedy for the diseases/infections caused by these organisms.